Bimbingan dan Konseling Islami dan Problem Mayarakat - Nadzmi Akbar, S.Pd., M.Pd.I (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2015)
Broadly speaking, the human problem consists of problems associated with itself, problems relating to others, problems related to the environment and the problem of the relationship with God. The inability of humans to adapt to the components mentioned above, causes people in trouble. Islamic Guidance is the process of providing assistance from a mentor (counselor / helper) to a client / helpee. In the implementation of the aid, a mentor / helper should not be overbearing or require client / helpee to follow what he suggested, but merely provide direction, guidance and assistance, and the assistance provided was more focused to help yag relating to psychiatric / mental and not relating to material or financial directly. Problems that occur in society in general are: personal problems, social problems, family problems, marital problems, problems of education, health and physical problems, problems of employment and careers, economic problems, problems of religion, relationship problems young couple. Guidance and counseling is an attempt to avoid and alleviate problems in the community. Guidance and counseling have a function that is a function of prevention, alleviation, understanding, preservation and distribution, and advocacy.